SI-PENYU: SISTEM PENGELOLAAN KELAUTAN BERUPA USV SEMI-AUTOMATIC PENDETEKSI MINYAK DAN IKAN - Fawzia, Meuthia; Azhar, Firdhaus; Ningsih, Ary Kusuma; Devianto, Kristiawan; Fattah, Muhammad Nur (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
SI-PENYUâs system can be used to determine which waters are containing a lot of fish as well as the detection of oil spills. This detection system uses sonar sensors that can send and capture signals from the object, then process it in a minimum system to inform the ground station and the data will be obtained. SI-PENYUâs system is semi-automated means that can be automatically or manually controlled. If the system works automatically, it will move through the SI PENYU way point of the coordinate. Automatic addition, this tool can also work manually controlled by a remote controller from the ground station.